Timing of Haemophilus influenzae type b vaccination after cardiac surgery. Issue 8 (8th March 2016) - Takanashi, Manabu; Ogata, Shohei; Honda, Takashi; Nomoto, Keiko; Mineo, Eri; Kitagawa, Atsushi; Ando, Hisashi; Kimura, Sumito; Nakahata, Yayoi; Oka, Norihiko; Miyaji, Kagami; Ishii, Masahiro
Abstract: Background: The best time for vaccination in infants with congenital heart disease (CHD) after cardiopulmonary bypass (CPB) surgery is unclear, but it is important to prevent Haemophilus influenzae type b (Hib) infection in infants with CHD after CPB surgery. To identify the best time for Hib vaccination in infants with CHD after CPB surgery, we investigated the immunological status, and the efficacy and safety of Hib vaccination after CPB surgery. Methods: Sixteen subjects who underwent surgical correction of ventricular septal defect with CPB were investigated. Immunological status and cytokines were analyzed before surgery, 2 months after surgery, and before Hib booster vaccination. Hib‐specific IgG was also measured to evaluate the effectiveness of vaccination. Results: Immunological status before and 2 months after surgery (e.g. whole blood cells and lymphocyte subset profile) was within the normal range and no subjects had hypercytokinemia. Additionally, all subjects who received Hib vaccination at 2–3 months after CPB surgery had effective serum Hib‐specific IgG level for protection against Hib infection without any side‐effects. Conclusions: CPB surgery does not influence acquired immunity and Hib vaccination may be immunologically safe to perform at 2 months after CPB surgery. Hib vaccination at 2–3 months after CPB surgery was effective in achieving immunization for infants with simple left–right shunt‐type CHD.